The Effect of Perceived Behavioral Control, Perceived Served Quality, Intention, and Trust on Zakat Compliance Behavior Mediated by Religiosity - Takdir Takdir; Muhammad Nur Alam Muhajir; Erwin Erwin; Muzayyanah Jabani (Ekonomi Syariah IAIN Kudus, 2023)
This study evaluates the relationship between perceived behavior control, perceived served quality, and zakat compliance behavior by using religiosity as a moderating variable and intention and trust as mediating variables. This study employs quantitative research by using a structured questionnaire from 200 Indonesian Muslim community respondents who are obligated to pay zakat al-Fitr and or zakat on wealth as a purposive sampling with specific criteria. The collected data are then analyzed using SEM-PLS. The results of the study reveal a significant effect of perceived behavior control on the intention with a significance value of less than 0.05 (0.000<0.05), and religiosity does not moderate the relationship between perceived behavior control and intention with a significance value of 0.374 (0.374>0.05). This study further shows that intention, perceived served quality, and trust have an effect on zakat compliance behavior with a significance value of less than 0.05 (0.000<0.05). Meanwhile, perceived served quality does not affect zakat compliance behavior (0.861>0.05). Furthermore, intention mediates the relationship between perceived behavior control and zakat compliance behavior (0.003<0.05), and trust mediates the relationship between perceived served quality and zakat compliance behavior with a significance value of less than 0.05 (0.000 <0.005). This study makes two distinct contributions in the areas of empirical analysis and policy implications. The results of this study contribute to the existing body of literature related to empirical evidence for the development of the Zakat compliance behavior model. In addition, it has the potential to facilitate the sustainable growth of zakat institutions.